Предучилишното воспитание на децата со пречки во развојот – предуслов за успешно интегративно образование - Јачова, Зора; Солтирова, Елизабет; Икономова, Славица; Чичевска, Наташа; Георгиева, Наташа (Филозофски факултет, Скопје, 1997)
Pre-school upbringing of children with developmental difficulties is the first link in the system of education and upbrining and at the same time the utmost segment in the system of integrational rehabilitation. Initiating the process of pre-school upbringing and adequate organized treatment at early age, permits support of the development and maximum usage of the remained capabilities of children with developmental difficulties. The newest world experiences show that the upbringing and educational integration of children with developmental difficulties as asegment of the social integration, should set the main conditions in the frames of upbringing education and rehabilitational continuity and support the minimal restrictive environment for their development. In the pre-school institutions that function on the territory of the Republic of Macedonia, an indifferent attitude towards the children with developmental difficulties is present, due to the uninformed educators for the characteristics and capabilities of these children and their believes for the negative influence of the children with developmental difficulties on the children without impairments, that implicates involvement of subsidery defectological education of present employed staff in the mainstream pre-school institutions, also including defectologists in kindergartens for work with children with special difficulties in their development. Also, the data about the educator’s attitude in the mainstream preschool institutions is disturbing, so that they put the accent on the obligation for reducing of the program for work with handicapped children, not taking into consideration that subsidery, special forms and methods are needed beside the programs that are for the main stream group. The goal of our paper is to point out the need of involving of children with light developmental difficulties; the existence of special team in the pre-school institutions when involving children with developmental difficulties in integrational conditions, will follow the child for a longer period and will enable interdisciplinary approach in diagnostics, work and evaluation of the capabilities of the child, like a base in planning of the upbringing and educational work with children at pre-school age.
Pre-school upbringing of children with developmental difficulties - а condition for successful integrational education